Derivatives in a cross-border context: a conflicts-of-laws analysis - Garcimartín Alférez, Francisco José; Sánchez Fernández, Sara (Leiden University, 2018)
In Derivatives in a cross-border context: a conflicts-of-laws analysis Francisco J. Garcimartí and Sara Sánchez Fernández analyse some of the conflict of laws issues that arise within the realm of derivative contracts in the EU.
Keywords: 56 Ciencias Jurídicas y Derecho::5603 Derecho internacional; ODS 16 - Paz, justicia e instituciones sólidas; ODS 8 - Trabajo decente y crecimiento económico; ODS 17 - Alianzas para lograr los objetivos